Horton River Band recorded at the Weekend of Traditional Australian Music in the Chris Sullivan folklore collection - Horton River Band (Musical group).; Sullivan, Chris (Christopher Daniel), 1953- (1988)
Folkloric recording.
Music collected, performed and presented by Mark and Cathy Rummery, Jacko Kevans, Barry McDonald, Geoff Lawrie, Maz Plane, Chris Sullivan and others.
Recorded in 1988, at South Stradbroke Island, Moreton Bay, Qld.
Digital master available
Keywords: Horton River Band (Musical group) -- Performances; Folk singers -- Australia -- Performances; Accordionists -- Australia -- Performances; Folk songs, English -- Australia; Folk dance music -- Australia; Folk music -- Australia; Singing; Folk singers; Folk musicians